Neurturin is a PGC-1α1-controlled myokine that promotes motor neuron recruitment and neuromuscular junction formation - Richard Mills; Hermes Taylor-Weiner; Jorge C. Correia; Leandro Z. Agudelo; Ilary Allodi; Christina Kolonelou; Vicente Martinez-Redondo; Duarte M.S. Ferreira; Susanne Nichterwitz; Laura H. Comley; Vanessa Lundin; Eva Hedlund; et al. (Elsevier, 2018)
Objective: We examined whether skeletal muscle overexpression of PGC-1α1 or PGC-1α4 affected myokine secretion and neuromuscular junction (NMJ) formation. Methods: A microfluidic device was used to model endocrine signaling and NMJ formation between primary mouse myoblast-derived myotubes and embryonic stem cell-derived motor neurons. Differences in hydrostatic pressure allowed for fluidic isolation of either cell type or unidirectional signaling in the fluid phase. Myotubes were transduced to overexpress PGC-1α1 or PGC-1α4, and myokine secretion was quantified using a proximity extension assay. Morphological and functional changes in NMJs were measured by fluorescent microscopy and by monitoring muscle contraction upon motor neuron stimulation. Results: Skeletal muscle transduction with PGC-1α1, but not PGC-1α4, increased NMJ formation and size. PGC-1α1 increased muscle secretion of neurturin, which was sufficient and necessary for the effects of muscle PGC-1α1 on NMJ formation. Conclusions: Our findings indicate that neurturin is a mediator of PGC-1α1-dependent retrograde signaling from muscle to motor neurons. Keywords: Skeletal muscle, PGC-1α, Neurturin, Motor neuron, Myokine